IMPLEMENTASI SISTEM INFORMASI PEMASARAN PRODUK SEPATU LOKAL HANDMADE BERBASIS WEB - Renaldi Prasetya; Mira Orisa; Nurlaily Vendyansyah (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
Almost all businesses are motivated to innovate in marketing or promoting their products in various ways. One of them is to use website. This is supported by the large number of internet users around the world, moreover as a medium of information, website-based applications are more accessible than desktop-based applications. Implementation of the website as a marketing needs to be applied to a local business like handmade leather shoes named Reeold. So far, it seems that leather shoes only have models that don't follow trends and it's rare to be able to order handmade shoes according to current models and youth trends, so Reeold comes with a new concept, namely handmade leather shoes that can follow the models and styles of young people. However, the problem is that there are more and more competitors making handmade shoes in Indonesia, so this business requires a digital platform that can be used in today's global business competition. Through a web-based information system, manufacturers can expand promotional activities and simplify the customer ordering process, so that sales of handmade shoe products are increasing.